2018
DOI: 10.20902/ijctr.2018.111040
|View full text |Cite
|
Sign up to set email alerts
|

Approximation of An Experimental Model Obtained in A Testing Machine for use in an Industrial Production Machine

Abstract: Design of experiments (DOE) is a powerful tool that allows performing the modeling and analysis of the influence of factors of the process on the specified variables, which are often called response variables. Being a systematic procedure to analyze the effect of the response variables, and the controllable factors that are modified during the execution of the experiment.Within the different strategies of the design of experiments, the factorial design is one of the most widely used. The problem with factorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In recent years, the empirical study of market price predictability has promoted the rise of behavioral finance. For example, Sargun et al [16] found that the price fluctuation in the U.S. stock market is too large to be explained by fundamental information; When Nguyen and Duong [17] studied the stocks on the New York Stock Exchange, they found that the stocks with the best performance in three to five years will have the lowest market adjusted return in the same period of time; Coba Salcedo et al [18] found that the dividend price ratio can significantly predict the future yield; and Pembury Smith and Ruxton [19] found that trading strategies based on price momentum over the past 3 to 12 months can obtain excess returns. In addition, many other studies have found that financial markets are predictable.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, the empirical study of market price predictability has promoted the rise of behavioral finance. For example, Sargun et al [16] found that the price fluctuation in the U.S. stock market is too large to be explained by fundamental information; When Nguyen and Duong [17] studied the stocks on the New York Stock Exchange, they found that the stocks with the best performance in three to five years will have the lowest market adjusted return in the same period of time; Coba Salcedo et al [18] found that the dividend price ratio can significantly predict the future yield; and Pembury Smith and Ruxton [19] found that trading strategies based on price momentum over the past 3 to 12 months can obtain excess returns. In addition, many other studies have found that financial markets are predictable.…”
Section: Related Workmentioning
confidence: 99%